Girls and Women in Mines: an Invisible Path of Forced Labour in Italy - Salerno, Silvana (La Medicina del Lavoro, 2025)
This study aims to shed light on the largely understudied history of girls and women working in Italian mines during the 19th and 20th centuries. Giovanni Loriga authored an outstanding paper on Pneumoconiosis in 1930 at the Johannesburg Conference. By examining his sources from earlier surveys, travel records, and congressional proceedings, the research uncovers data on women and girls in slate (Liguria), asbestos (Piedmont), zinc-lead (Sardinia and Lombardy), and sulfur mines (Sicily), along with their working conditions. The research findings reveal that girls and women were integral to the mining industry throughout Italy, despite being underrepresented and relegated to specific tasks. Ultimately, the paper explores the development of protective Italian legislation, its inadequate enforcement, and suspension during World War I. The paper concludes by highlighting the ongoing global issue of girls’ labour in mines, drawing a parallel between the historical situation in Italy and the contemporary reality denounced by organizations like the ILO and UNICEF.